THE COURSE 'PRACTICE OF EXPERIMENTAL METHODS IN MACHINING' - Kaufnerova, Aneta; Kutlwaser, Jan (Annals of DAAAM & proceedings, 2019)
This article is about the course 'Practice of experimental methods in machining'. This subject is taught at the Faculty of Mechanical Engineering of the University of West Bohemia, specifically at the Department of Machining. The main part of the article briefly describes the individual experiments and measuring devices used in the experiments. Furthermore, these experiments are described from the perspective of their contribution to students and the preparation of students for real industry. The last part of the article deals with the extension of practical teaching of the subject 'Practice of experimental methods in machining' by measuring self-excited oscillation. Keywords: education; experiments; measurement; cutting forces; vibration